Utilization of Quizizz Media as A Tool for Evaluation of Mathematics Learning Students of SDI Al-Chusnaini Sukodono - Mela Norma Yuniasti; Rulyansah, Afib; Hartatik, Sri; Mariati, Pance (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
This study was conducted to determine the implementation and obstacles in evaluating mathematics learning using the media quizizz for fourth grade students of SDI Al-Chusnaini Sukodono, East Java. This study uses descriptive qualitative research methods. This study describes the implementation and obstacles in evaluating mathematics learning using quizizz media for fourth grade students of SDI Al-Chusnaini Sukodono, East Java.The results of research conducted by researchers through observations and interviews with teachers and fourth grade students of SDI SDI Al-Chusnaini Sukodono, East Java, resulted in data that the evaluation of mathematics learning using quizizz media made evaluation activities fun but not effective because several things, including teachers could not knowing the working process of students when evaluating learning and there are some students experiencing problems related to signals or networks that are less stable.